AKTIVITAS INHIBITOR α-GLUKOSIDASE ISOLAT KAPANG ENDOFIT DUWET (Syzygium cumini (L.) Skeels) - Roseliana Fitri; Agung Suprihadi; Sri pujiyanto (Jurnal Akademika Biologi, 2016)
Java plum known to have the ability as a diabetes drug. The essence of diabetes treatment is to maintain blood sugar levels in normal state using α-glucosidase inhibitor. Such capabilities can be obtained from endophytic mould found in java plum plant. The aim of this study is to get the best isolates that have the ability of α-glucosidase inhibitors with different carbon sources. This study uses java plum endophytic mould isolates which tested the ability of α-glucosidase inhibitor by using spectrophotometric techniques with breaking substrates to produce colored products and a variety of carbon sources such as sucrose, lactose, maltose and starch. The results of α-glucosidase inhibitor activity indicate that crude extract of isolates JB 2.3 has the best ability to produce α-glucosidase inhibitor with a percentage of 13.76% is higher than the positive control acarbose 1%. Lactose be the best carbon source with a mean inhibition of (19.27%), sucrose (13.58%), starch (12.70%), Maltose (10.76%).Keywords: α-glucosidase inhibitor, endophytic mould, java plum, diabetes melitus.